Narrativa e representação: uma leitura de Cidade de Deus - Rocha, Renato Oliveira [UNESP] (2015)
This Master's thesis aims to analyze the relationship of the novel City of God (1997) with the reality it represents, to grasp how it gives a construction of the representation of reality, especially with respect to violence, through the narrative. The novel by Paulo Lins, one of the most important in Brazilian prose of the late twentieth century, can be taken as a fictional aspect that ushers realism in contemporary narrative. City of God brings out the Brazilian reality combining techniques of anthropological story in a fast pace, which deals with the development of drug trafficking and criminality in public housing that gives the book its title, signing the realistic contract with the reader. To give a formal treatment to the violent scenes, Paulo Lins makes use of poetry, beginning with the title-poem of Paul Leminski that the author uses in the opening of the book, providing a literary depiction of violence, however brutal it may be. This formal mediation that the writer uses to shape the depicted object provides a reading of the excluded Brazil and its realization in the novel, we can say, it appears as a separate chapter in the Brazilian literature and studies that would arise about the relationship between literature and poverty in Brazil. The insistence on violent scenes gives unity to the narrative, causes an effect of reality and leads the reader to think comprehensively in its significance, boosting the representation of violence as a constituent element of Brazilian society. Questioning the very notion of representation, what is sought is to discuss the novel in light of a diachronic perspective that considers how the realism - thought in the wake of proposing Tânia Pellegrini, such as posture and method - takes place in the novel in issue, distinguishing it - or not - than we might think as a realistic trend in Brazilian literature